2007
DOI: 10.1622/1059-8405(2007)023[0337:eoneof]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Nutrition Education on Fast Food Choices in Adolescents

Abstract: Adolescent obesity has become a major health concern in the United States. An increased frequency of fast food restaurant dining is associated with higher intake of calories and calories from fat. The purpose of this study was to gain insight as to how food choices in a "simulated" fast food environment might be influenced by nutrition education in a group of adolescents. Ten adolescents were asked to choose food items from a fast food restaurant menu. Their chosen meals' nutrition make-up (calories, fat, chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 0 publications
4
15
0
Order By: Relevance
“…This finding is consistent with Allen et al (41) and Cox et al (42) . It is noteworthy that despite the increase of energy, vitamin A, vitamin C and Ca intakes in the experimental group after the intervention, the intake amount is still inadequate and below the standards.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with Allen et al (41) and Cox et al (42) . It is noteworthy that despite the increase of energy, vitamin A, vitamin C and Ca intakes in the experimental group after the intervention, the intake amount is still inadequate and below the standards.…”
Section: Discussionsupporting
confidence: 92%
“…Also, students had a low nutritional knowledge about the fast foods and their harms [26] . Likewise, in a research conducted in 2014 by Allen et al, it was found that students had a low nutritional knowledge about fast foods and complications of these types of foods [27] . students of Shahid Beheshti University evaluating the knowledge and attitude of students towards fast food consumption, it was found that 21.9 students are in poor or very poor level of knowledge to the fast foods [28] .…”
Section: Discussionmentioning
confidence: 97%
“…Roger in [5] states that knowledge / cognitive is a very important domain in the formation of behavior in this case the prevention of drug use in teenagers, and behavior based on knowledge will survive more lasting than the behavior that is not based on knowledge. Allen's [6]study reveals that one's knowledge will affect the health behavior of the person, the training program to further empower Dasa Wisma done by the researcher on the group members of the treatment group is aimed at improving health behavior towards the positive, and the behavior will persist when the individual realizes the importance Positive health behavior is very beneficial in everyday life. In IVCN this study, the knowledge of respondents in the treatment group experienced a better improvement compared to the control group with a value of P = 0.000.…”
Section: Dasa Wisma Programs Related To the Prevention And Control Ofmentioning
confidence: 99%